2012
DOI: 10.1088/0004-637x/759/1/50
|View full text |Cite
|
Sign up to set email alerts
|

The Abrupt Changes in the Photospheric Magnetic and Lorentz Force Vectors During Six Major Neutral-Line Flares

Abstract: We analyze the spatial and temporal variations of the abrupt photospheric magnetic changes associated with six major flares using 12-minute, 0. 5 pixel −1 vector magnetograms from NASA's Helioseismic and Magnetic Imager instrument (HMI) on the Solar Dynamics Observatory satellite. The six major flares occurred near the main magnetic neutral lines of four active regions, NOAA 11158, 11166, 11283 and 11429. During all six flares the neutral line field vectors became stronger and more horizontal, in each case alm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
74
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 23 publications
(44 reference statements)
22
74
1
Order By: Relevance
“…The two main darkening/decaying areas, "E" and "D," indicated by the white/black arrows and enclosed by the white/black boxes, can be more obviously discerned in the difference intensity image (panel (c)), in which dark/bright features indicate enhancing/decaying areas in the post-flare image. In line with some previous observations (Wang & Liu 2010;Liu et al 2012;Petrie 2012), outstanding changes in the horizontal components of vector fields, B h , also took place in E and D. In order to exhibit these changes distinctly and concretely, in the vector magnetograms (panels (d1) and (d2)), the vertical components of vector fields, B r , are plotted as grayscale background superposed with isogauss contours, while the horizontal components are represented by the short arrows aligned to the field direction, with varying color proportional to the different field strengths as indicated by the color bar. For clarification, B h | | less than 400 G are not overplotted.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The two main darkening/decaying areas, "E" and "D," indicated by the white/black arrows and enclosed by the white/black boxes, can be more obviously discerned in the difference intensity image (panel (c)), in which dark/bright features indicate enhancing/decaying areas in the post-flare image. In line with some previous observations (Wang & Liu 2010;Liu et al 2012;Petrie 2012), outstanding changes in the horizontal components of vector fields, B h , also took place in E and D. In order to exhibit these changes distinctly and concretely, in the vector magnetograms (panels (d1) and (d2)), the vertical components of vector fields, B r , are plotted as grayscale background superposed with isogauss contours, while the horizontal components are represented by the short arrows aligned to the field direction, with varying color proportional to the different field strengths as indicated by the color bar. For clarification, B h | | less than 400 G are not overplotted.…”
Section: Resultssupporting
confidence: 92%
“…In more recent years, high-resolution white-light sunspot observations revealed some changes in photospheric fine structures caused by flares, e.g., disappearing penumbra fibrils and transition bright grains could evolve into faculae (Wang et al 2012a), granulation pattern could evolve to alternating dark and bright penumbra fibril structures (Wang et al 2013), and there were remarkable high-speed flows along the flaring PILs (Shimizu et al 2014). On the other hand, the photospheric vector magnetic-field observations showed that the horizontal magnetic fields increased rapidly and permanently around the central PILs (Wang & Liu 2010;Liu et al 2012;Petrie 2012;Sun et al 2012;Wang et al 2012bWang et al , 2012c, while they decreased significantly in the outer regions (Wang et al 2009;Li et al 2011;Sun et al 2012). These results thus suggested that, after major flares, the magnetic fields often became more horizontal in the central PIL regions but more vertical in the decaying penumbra regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They note: "Immediately prior to the eruption, the model field contains a compact sigmoid bundle of twisted flux that is not present in the post-eruption models." The study by Petrie (2013) shows that the high-R PIL, and in particular structures around the end points of the inferred flux rope, are locations where the horizontal field component increased (also noted by Sun et al 2012), and the Lorentz force shows the most pronounced change when comparing pre-and post-flare vector magnetograms (also seen in flares in ARs 11166, 11283, and 11429 described in subsequent sections, see Petrie 2012) The sunspot linked to the X2.2 flare was rotating, as was another adjacent to an M2.2 flare on the day before: Li & Liu (2015) note that the M2.2 flare occurs when the spot rotation rate peaks. Kazachenko et al (2015) estimate Poynting fluxes in a 6 day sequence of photospheric vector-magnetic maps observed by SDO/HMI to conclude that the estimated free energy of 2 10 32 »´erg is compatible within better than a factor of two with the energy needed for the X-class flare on 2011 February 15 and with other estimates of the free energy (see references in their paper).…”
Section: Ar 11158mentioning
confidence: 69%
“…Hudson, Fisher, and Welsch (2008) noted that explosive events should decrease coronal magnetic energy and thus lead the coronal field to contract, increasing the inclination angle or the angle between the vertical and horizontal photospheric field. Indeed, several studies Petrie, 2012Petrie, , 2013Sun et al, 2012;Wang, Liu, and Wang, 2012) showed that the horizontal component of the magnetic field changes within select areas of an active regionin particular, near the polarity-inversion line. However, the mean inclination angles shown in the lower-right panel give no indication of an obvious systematic relationship to flare size or timing.…”
Section: Tablementioning
confidence: 99%